The effect of a task-specific locomotor training strategy on gait stability in patients with cerebellar disease: a feasibility study. Issue 10 (8th May 2017) - Im, Seung-Jin; Kim, Yong-Hyun; Kim, Kwon-Hee; Han, Jae-Woong; Yoon, Sung-Jin; Park, Jin-Hoon
Abstract: Purpose: There is a lack of evidence-based recommendations for the physiotherapeutic intervention specifically for locomotor training in patients with cerebellar ataxia. The purpose of this study is to determine the feasibility and effect of a more specific rehabilitation strategy that aims to improve gait quality in patients with cerebellar ataxia. Methods: Nineteen patients with degenerative cerebellar ataxia were recruited to participate in the study. The patients participated in a 12-week locomotor training program, two times per week for 1.5 h per session (a total of 24 training sessions). The treatment approach emphasized the relearning of proper gait movement strategies through intensive practice that enhances the patient's perception and control of the essential components of normal gait movement. Results: A quantitative analysis of step-by-step gait performance indicated that postural sway during locomotion was reduced, and the gait movement pattern became more consistent after the 12-week locomotor training program. These improvements in gait stability persisted over the 3-month period following intervention. Conclusion: This study provides preliminary evidence that learning-based rehabilitation strategies targeting disease-specific locomotion symptoms may be helpful for reducing ataxic gait and improving motor control during walking in patients with cerebellar dysfunction. Implications for rehabilitation: Physiotherapeutic interventions that aim to promote gait stability in cerebellar patients need to create a specific learning context that improve disease-related gait deficits. It is desirable to use explicit instructions to facilitate the conscious awareness and control of body center and posture. As patients reacquire the fundamental gait ability, providing training experience with various locomotor tasks that facilitate the transfer of learning may be helpful to increase generalizability of locomotor intervention.